Drug‐eluting beads versus conventional chemoembolization for the treatment of unresectable hepatocellular carcinoma. Issue 3 (26th February 2016) - Facciorusso, Antonio; Mariani, Luigi; Sposito, Carlo; Spreafico, Carlo; Bongini, Marco; Morosi, Carlo; Cascella, Tommaso; Marchianò, Alfonso; Camerini, Tiziana; Bhoori, Sherrie; Brunero, Federica; Barone, Michele; et al.
Abstract: Background and Aim: Solid demonstrations of superior efficacy of drug‐eluting beads transarterial chemoembolization with respect to conventional chemoembolization in hepatocellular carcinoma patients are lacking. The aim of the study was to compare these two techniques in two large cohorts of unresectable hepatocellular carcinoma patients. Methods: A single center series of 249 early/intermediate hepatocellular carcinoma patients who underwent "on demand" chemoembolization in the period 2007–2011 was analyzed. Overall survival, time to progression, tumor response rate, and safety were compared between 104 patients who underwent conventional chemoembolization and 145 who underwent drug‐eluting beads chemoembolization. Time‐to‐event data were analyzed using the Cox univariate and multivariate regression. Results: The two cohorts resulted balanced for liver function and tumor stages. Objective response rate was 85.3% after conventional and 74.8% after drug‐eluting beads chemoembolization ( P  = 0.039), and median time to progression was 17 (95% confidence interval: 14–21) versus 11 months (9–12), respectively ( P  < 0.001). Treatment regimen was the sole independent predictor of progression at multivariate analysis (hazard ratio = 2.01; 1.45–2.80; P  < 0.001). Median survival was 39 (32–47) and 32 (24–39) months in the two groups, respectively (hazard ratio = 1.33; 0.94–1.87; P  = 0.10), but conventional chemoembolization was significantly associated with a survival advantage in patients with bilobar neoplasia, portal hypertension and alpha fetoprotein above normal limits. No significant differences in severe adverse events were found. Conclusion: In a large series of Western hepatocellular carcinoma patients, drug‐eluting beads chemoembolization with 100–300 µm particles did not seem to improve survival in comparison with conventional chemoembolization, which in turn provided better tumor responses and time to progression.